The Antecedents of Financial Literacy of Homestay Entrepreneurs - Towiyah, Towiyah; Kaukab, M. Elfan (International Journal Accounting Tax and Business, 2020)
Objectives - This study aims to analyze the level of financial literacy of homestay entrepreneurs in Wonosobo District, viewed from the aspects of basic knowledge of financial management, credit and savings management, investment management, risk management, and analyzing the level of financial literacy seen from all aspects. Methodology - This study uses a descriptive qualitative approach with a population of all homestay business owners in Wonosobo Regency. Research samples of 33 people were taken by simple random sampling technique. Data collected by the method of observation, interviews, and documentation. Analyzed with reduction techniques, interpretative data presentation, and concluding. Results of the study - It was concluded that the average homestay business actor in Wonosobo District had a moderate level of financial literacy in 1) aspects of basic knowledge of financial management and 2) aspects of credit and savings management, and low in 3) aspects of investment management and 4) aspects of risk management, and 5) when viewed from all aspects, homestay entrepreneurs in Wonosobo Regency have a moderate level of financial literacy. Implication - Expanding public access to financial institutions to increase public interaction with financial technology, delivery channels for financial products and services, and socialization from related parties is expected to be able to encourage increased public financial literacy. Limitation - This study is still limited to 33 of the 95 people registered to have a homestay business in Wonosobo. So it is recommended for future studies to increase the number of respondents so that the data generated is much closer to the actual conditions. Originality- Research on the financial literacy of MSMEs in the homestay sector in Wonosobo Regency has never been conducted before. Keywords: Financial Literacy, Financial Management, Credit and Savings, Investment, Risk Management, Homestay